(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
In the XV century the Duchy of Milan was engaged in long and bloody conflicts, especially against Venice, which threatened Milan itself. Besides the armies of the condottieri, there was another important component for the military of the Duchy: the river and lake fleet, which counted dozens of ships, from light to heavy ones, like galleons. the Milanese fleet had very important roles during the wars: surveillance of the territory, defense against raids from enemy ships, pillage of enemy towns and harbours, support to land armies. the fleet often fought against Venetian one in bloody battles, whose results could change the balance of entire conflicts. Burocratic machinery for the reparations of ships and docks and chains of commands were created around the fleet, which held an essential role during the constant and ferocious wars of the XV century. DOI 10.17464/9788867743346